Estimation of the Source Parameters of the Flores Earthquake and Their Correlation to Aftershocks - Emanuel Destianus Banggut; Bagus Jaya Santosa (IPTEK The Journal of Engineering, 2019)
This study uses data provided by BMKG Indonesia which is downloaded from the website www.webdc.eu. The data processing is done by using some software, one of them is Matlab to run Isola software. The software provides information about the fault direction. In addition, this study also uses Coulomb 3.3 software to provide information on subsequent earthquake forecasts. The results showed that the earthquake that occurred on 27th February 2015 gave impact to Coulomb's increase and decrease of stress to some areas in the northern mainland of Flores. The impact of this major earthquake is expected to trigger an earthquake that occurred in northern Flores. Based on the results of data processing obtained form focal mechanism is oblique reverse with the first nodal value strike 139, dip 73, and rake 50. While on the second nodal has a strike value 30, dip 43, and rake 154. Main earthquake impact Coulomb stress increase of 0.15-0.2 bar. Meanwhile, Coulomb stress result obtained shear value -18.890, normal -0.217, and Coulomb -19.976.